(untitled) (Research, Society and Development, 2020)
Sarcopenia is characterized by reduced muscle mass, associated with decreased muscle strength or physical performance and presents itself as an important problem that affects individuals over the years. In the current context, nutrition and physical activity have stood out as important pillars for the prevention and treatment of this frailty syndrome. The study aimed to analyze how good consumption related tô the diagnosis of sarcopenia, the food consumption of the elderly and their relationship with the diagnosis of sarcopenia, noting which are the main nutrients that are involved in this process. It is an integrative review, with a systematic search, carried out through the Pubmed databases; Scientific Electronic Scientific Library Online (SCIELO) scientific library; Latin American and Caribbean Literature on Health Sciences (LILACS) and Web of Science. The search terms were “Elderly, Nutrients, Sarcopenia and Eating”. Initially, a total of 530 publications was obtained, after careful evaluation the final sample consisted of 6 articles. Despite the lack of standardization of studies, it was observed that the consumption of inadequate proteins, micronutrients and minerals, especially vitamin D, E, A, B, magnesium, selenium, potassium, calcium and zinc, are involved in the diagnosis of sarcopenia, as well as a Mediterranean eating pattern is associated with reduced risk. The need for studies using standardized methods is emphasized in order to enable more reliable comparisons between results and of a longitudinal character.